Evaluación de la pertinencia entre los logros de aprendizaje y el perfil profesional de los estudiantes, de la carrera de análisis de sistemas del instituto tecnológico superior Ismael Pérez Pazmiño durante el periodo lectivo 2012-2013, y propuesta de mejoramiento del plan curricular institucional. - Torres Illescas, Jéssica Azucena (2013)
The problem of assessing the relevance between learning achievement and professional profile of students , career analysis systems superior technological institute Ismael Pérez Pazmiño is necessary investigate , a situation that requires students to master in Teaching university and Educational Research , conducted a process of critical and self-critical of the relevance between learning achievement and professional student profile analysis , taking into account, to the extent that these aspects are linked , contributing to strengthening the quality training students to scientific, technical and humanistic level corresponding to their future professional field performance.